Country Kids, City Kids: Community Context and Geopolitical Identity - Jan Armstrong Gamradt; Patricia G. Avery (Journal of Research in Rural Education, 1991)
This study examines whether community context shapes geopolitical identity. An open-ended survey was administered to 187 rural and urban tenth grade students by their social studies teachers. Students were asked to describe their community, state, nation, and world. Participants'responses were analyzed using content analytic techniques. Comparison of rural and urban students' responses revealed both continuities and discontinuities. Implications for rural education and rural education research are discussed.